2013
DOI: 10.1186/1746-1596-8-154
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotypic features and t(14;18) (q32;q21) translocation of Chinese follicular lymphomas helps to distinguish subgroups

Abstract: BackgroundThe revised 2008 World Health Organization classification maintains a histological grading system (grades 1–3) for follicular lymphoma (FL). The value of grading FL has been debated. This study will yield deeper insights into the morphologic, immunophenotypic characterization and t(14;18) translocation in FL and explore their significance of diagnosis of Chinese FL subgroups.MethodsWe retrospectively reviewed the FL diagnoses according to the 2008 WHO classification in all diagnostic specimens from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The t(14;18)(q32;q21) chromosomal abnormality involves the immunoglobulin heavy chain (IGH) gene on chromosome 14q32 and the B-cell CLL/BCL2 gene on chromosome 18q21, and results in BCL2 being placed under the regulatory control of the IgH promoter leading to overexpression of the BCL2 protein (7). It is considered the genetic hallmark of FL and is identified in ≤90% of FL cases (7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The t(14;18)(q32;q21) chromosomal abnormality involves the immunoglobulin heavy chain (IGH) gene on chromosome 14q32 and the B-cell CLL/BCL2 gene on chromosome 18q21, and results in BCL2 being placed under the regulatory control of the IgH promoter leading to overexpression of the BCL2 protein (7). It is considered the genetic hallmark of FL and is identified in ≤90% of FL cases (7).…”
Section: Discussionmentioning
confidence: 99%
“…It is considered the genetic hallmark of FL and is identified in ≤90% of FL cases (7). Although present in the majority of FL patients, using a standardized, highly sensitive quantitative polymerase chain reaction technique, t(14;18)(q32;q21) may be identified at low frequencies in ≤70% healthy individuals, suggesting that BCL2 overexpression is required but not sufficient for FL development (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the change of chromosome karyotype is an important independent risk factor for NHL prognosis in addition to its histological implications (Chen et al, 2013). One study has shown multiple critical chromosome karyotype changes in NHL patients, and their significant effect on patient treatment efficacy and median survival period (Zhang et al, 2013). Certain complex changes in chromosome karyotype or rearrangement, and some special chromosome genesis abnormalities such as t(8:14)(q24:q32) translocation and +7, are unfavorable prognostic factors for NHL (Kahl and Yang, 2008;Zhang et al, 2010. Certain basic studies have shown no dysfunction of known genes located in the 6q21-25 region in NHL patients.…”
Section: Discussionmentioning
confidence: 99%